Endophthalmitis at a tertiary referral center: Characteristics and treatment outcomes over three decades - Zhang, Wen-Fei; Zhao, Xin-Yu; Meng, Li-Hui; Chen, Huan; Chen, You-Xin (Frontiers in Cell and Developmental Biology, 2022)
Purpose: To explore the incidence, pathogens, treatment and prognosis of endophthalmitis. Methods: Patients with the diagnosis of endophthalmitis from January 1990 to October 2020 at Peking Union Medical College Hospital were retrospectively reviewed and analyzed. Subgroup analysis was conducted regarding different initial treatment methods for eyes without concurrent retinal detachment (RD) at presentation. Results: A total of 249 eyes of 233 patients were included in this retrospective study. The most common clinical scenario was exogenous endophthalmitis (60.6%). The most frequent bacteria and fungi were coagulase-negative staphylococci (10.0%) and candida (6.8%), respectively. Retinal with/without choroid detachment was the most common complication after treatment. Patients with endogenous endophthalmitis were more likely to be binocular involvement and more patients with diabetes mellitus (DM) or immunosuppressive diseases, and the prognosis of VA was poorer. For eyes with concurrent RD at presentation, more eyes underwent serious complications after treatment (P < 0.05) and the visual outcome was worse than that without concurrent RD (P < 0.05). Subgroup analysis was conducted according to different initial treatments in eyes without concurrent RD. Group 1 received pars plana vitrectomy (PPV) with intravitreal injection of antibiotics (IVI) as initial treatment, Group 2 was initially treated with IVI only, and Group 3 was initially treated with nonsurgical treatment. More eyes that initially received IVI alone and non-surgical treatment required additional treatments, especially additional PPV. Visual acuity (VA) in both Group 1 and 2 significantly improved by the final VA. However, there was no significant difference in final VA between the two groups. There was an insignificant trend that serious post-treatment complications were more common in Group 1. In Group 1, 17 eyes received silicone oil or gas tamponade at the same time, while 62 did not. For eyes initially treated with PPV+IVI while without tamponade, they need more additional treatments and additional IVI. Conclusion: Endophthalmitis is a devastating intraocular disease and needs early intervention. Endogenous endophthalmitis has a poorer visual prognosis than exogenous entity. PPV + IVI as an initial treatment may reduce additional therapy.